Effect of mixing proportion on compressive strength of fly-ash based geopolymer paste and mortar using Taguchi’s method - Khan Afridi, S.; Vimonsatit, Vanissorn (ISEC Press, 2015)
Alkali activated pozzolan are known low carbon cementitious binders which can be used to replace cement. The material is also known as geopolymer because of its three dimensional polymeric chain and ring like structure consisting silica and alumina. A common type of pozzolan used is fly ash because of its rich silica content; therefore the term alkali activated fly-ash based binders is adopted. Despite much research and development of this material, there is no specific standard for design mix proportion. This research used the Taguchi’s design of experiment method to determine the optimum mix proportion of alkali activated fly ash based cement paste and mortar. Four factors were considered in the tests, silica fume, sand to cementitious ratio, liquid to solid ratio, and percentage of superplasticiser. Tests were conducted on the 9 batches of alkali activated fly-ash based paste and mortar samples to determine the compressive strength under ambient condition. Tests were also conducted to determine the residual strength of the samples after exposed to elevated temperatures. ANOVA analysis of the test results revealed the main factors contribution on the tested properties and led to the determination of the optimum design proportion of the factors considered in these tests.